Расчёт размерности регулярных фракталов в метрической зоне - Чумак, В. С.; Онищенко, А. А. (My University, 2019)
One non-trivial example is the fractal dimension of a Koch snowflake. It has a topological dimension of 1, but it is by no means a rectifiable curve: the length of the curve between any two points on the Koch snowflake is infinite. No small piece of it is line-like, but rather it is composed of an infinite number of segments joined at different angles. The fractal dimension of a curve can be explained intuitively thinking of a fractal line as an object too detailed to be one-dimensional, but too simple to be two-dimensional.
Keywords: размерность Хаусдорфа-Безиковича; размерность Минковского; структура фрактальная